Study protocol for the implementation of Centering Patients with Fibroids, a novel group education and empowerment program for patients with symptomatic uterine fibroids - Nyia L. Noel; Jasmine Abrams; Estefania Rivera Mudafort; Anagha Babu; Emma Forbes; Lauren Hill; Cherie C. Hill; Tanika Gray Valbrun; Nkem Osian; Lauren A. Wise; Wendy Kuohung (BMC, 2024)
Abstract Background Black women and people with uteri have utilized collectivistic and relational practices to improve health outcomes in the face of medical racism and discrimination for decades. However, there remains a need for interventions to improve outcomes of uterine fibroids, a condition that disproportionately impacts Black people with uteri. Leveraging personalized approaches alongside evidence that demonstrates the positive impact of social and peer support on health outcomes, we adapted from CenteringPregnancy, an evidence based group prenatal care intervention, for the education and empowerment of patients with uterine fibroids. Methods The present report provides  an overview of the study design and planned implementation of CPWF in cohorts at Boston Medical Center and Emory University / Grady Memorial Hospital. After receiving training from the Centering Healthcare Institute (CHI), we adapted the 10-session CenteringPregnancy curriculum to an 8-session hybrid group intervention called Centering Patients with Fibroids (CPWF). The study began in 2022 with planned recruitment of six cohorts of 10-12 participants at each institution. We will conduct a mixed methods evaluation of the program using validated survey tools and qualitative methods, including focus groups and 1:1 interviews. Discussion To date, we have successfully recruited 4 cohorts at Boston Medical Center and are actively implementing BMC Cohort 5 and the first cohort at Emory University / Grady Memorial Hospital. Evaluation of the program is forthcoming.